Chimera state in coupled map lattice of matrices - Mačernytė, Kotryna; Šmidtaitė, Rasa (Lietuvos matematikos rinkinys, 2021)
In recent years, a lot of research has focused on understanding the behavior of when synchronous and asynchronous phases occur, that is, the existence of chimera states in various networks. Chimera states have wide-range applications in many disciplines including biology, chemistry, physics, or engineering.The object of research in this paper is a coupled map lattice of matrices when each node is described by an iterative map of matrices of order two. A regular topology network of iterative maps of matrices was formed by replacing the scalar iterative map with the iterative map of matrices in each node. The coupled map of matrices is special in a way where we can observe the effect of divergence. This effect can be observed when the matrix of initial conditions is a nilpotent matrix.Also, the evolution of the derived network is investigated. It is found that the network of the supplementary variable $μ$ can evolve into three different modes: the quiet state, the state of divergence, and the formation of divergence chimeras. The space of parameters of node coupling including coupling strength $ε$ and coupling range $r$ is also analyzed in this study. Image entropy is applied in order to identify chimera state parameter zones.
Keywords: iterative map of matrices; logistic iterative map; chimera; nilpotent matrix; nilpotent; idempotent; divergence